Sex preselection of sheep using mineral solution injection via subcutaneous - Edres Abdulla Hamadamen; Abdulqader Ahmed Hussein (Zanco Journal of Pure and Applied Sciences)
The injection on Calcium (Ca) and Magnesium (Mg) solution is regarded as a method that have been conducted for sex preselection in sheep. Therefore, this trail was aimed to examine the effect of macro minerals such CaMg subcutaneous injected to Kurdish breed ewes during pre and post mating on lamb sex ratio skewing toward female. Thirty ewes at cycling multiparous period (based on their age and live weight (LW)) were randomly divided into two groups (15 ewes per group). Weekly (for four weeks) from four weeks’ days pre- to one week post-mating, each ewe (CaMg group) were subcutaneous injected by 30 ml of CaMg solution or sterile water (control group). Ewes live weigh at the end of the study were numerically higher (2.55 kg) in ewes injected with CaMg compared to control group. The serum ca and Mg were higher (P<0.05) in ewes administrated with CaMg solution than those not administrated. The level of total protein, urea, glucose, and cholesterol at blood serum were not affected (P>0.05) by CaMg injection. Reproductive hormone such estrogen was not different between control and injected ewes (P>0.05). Although, progesterone (at CIDR removal period) were increased (P<0.05) in injected ewes than control ewes. The new female born lambs were 2 times higher (P<0.05) in CaMg group compared to control group. The results of current study confirm that increasing the mineral proportion (Ca and Mg) in the ewes around mating via subcutaneous injection could skew sex ratio toward female in sheep. Thus, the findings of this trial might assist farmers in managing their breeding toward female lambs (which are going to be born in fattening enterprises and male milk production). More research is required to test different methods of altering mineral concentration and investigate the link between minerals in the diet and human sex pre-selection.